Stressors rendering school coexistence difficult, personal variables and burnout: towards an explanatory model (European Journal of Education and Psychology, 2010)
The main objective of this study is analyze the inter-relationships between the main stressors posing difficulties for school coexistence (students’ disruptive behavior, the teachers’ perception of a lack of social support and conflict), different personal variables (Type A behavior pattern, optimism, hardiness) and burnout. Furthermore, personal variables will be tested to see whether they mediate the influence of the different sources of stress analyzed in burnout. From the results obtained, using a sample of 1537 secondary education teachers, the co-variation between the different sets of variables analyzed is not only confirmed but also significant support is given for the mediation hypothesis (stressors would have an indirect influence on burnout through personal variables). Another interesting finding is the need to include in the resulting model a direct effect between the students’ disruptive behavior and the teacher’s burnout experience. In short, the resulting path confirms the personal variables analyzed as a necessary filter in the analysis of the stressors-burnout link, while at the same time integrating the direct effect that students’ disruptive behavior has on teacher’s occupational malaise.